Temple of the Sun - Thomas, Emma. (Milwaukee, Wis. : Gareth Stevens Pub., 2004)
Describes a research expedition to study Incan textile fragments and other artifacts in Peru.
Includes bibliographical references (p. 32) and index.
6.0
3-6
Keywords: Incas -- Peru -- Cuzco -- Antiquities -- Juvenile literature; Archaeology; Incas -- Antiquities; Indians of South America -- Antiquities; Archaeology; Incas -- Antiquities; Native Americans -- Peru; Native Americans -- South America; Coricancha Temple Site (Cuzco, Peru) -- Juvenile literature; Cuzco (Peru) -- Antiquities -- Juvenile literature; Machu Picchu Site (Peru) -- Juvenile literature; Coricancha Temple Site (Cuzco, Peru); Machu Picchu Site (Peru); Peru -- Antiquities; Coricancha Temple Site (Cuzco, Peru); Machu Picchu Site (Peru); Peru -- Antiquities